2022
DOI: 10.1108/jacpr-10-2021-0645
|View full text |Cite
|
Sign up to set email alerts
|

Violence against emergency healthcare workers: different perpetrators, different approaches

Abstract: Purpose This study aims to investigate whether emergency health-care workers distinguish between different categories of perpetrators of violence and how they respond to different types of perpetrator profiles. Design/methodology/approach Five focus groups with emergency health-care workers were held in Canada. The participants were asked whether they identified different groups of perpetrators of violence and how that impacted their approach. The focus group responses were transcribed verbatim and analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…HCWs in this study responded differently given the source of verbal aggression, indicating both understanding and lack of tolerance. This is similar to research done with paramedics who categorized reasons for aggression among patients, accepting some, such as dementia, and rejecting others, including substance abuse (Spelten et al , 2022). Further, participants pointed to COVID-related frustrations increasing the frequency of verbal aggression both in-person and by phone.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…HCWs in this study responded differently given the source of verbal aggression, indicating both understanding and lack of tolerance. This is similar to research done with paramedics who categorized reasons for aggression among patients, accepting some, such as dementia, and rejecting others, including substance abuse (Spelten et al , 2022). Further, participants pointed to COVID-related frustrations increasing the frequency of verbal aggression both in-person and by phone.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, some also indicated use of crisis management skills, indicating the value of training. This finding is similar to that of Spelten et al (2022), who reported paramedics believed their training helped them with de-escalation but differs from the work of Child and Sussman (2017), where emergency nurses questioned the efficacy of mandatory behavior modification courses.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, our findings raise important questions about how society should respond to acts of violence perpetrated against paramedics and other healthcare providers or first responders. Although the paramedic context may be more amenable to measurement, the issue of violence in healthcare settings is in no way unique to paramedicine [39,40]. There have been calls from professional associations representing physicians [41], nurses [42], and other healthcare professionals to address growing reports of hostility toward healthcare providers during the COVID-19 pandemic [43].…”
Section: Discussionmentioning
confidence: 99%
“…They also worry about specific emergency situations arising, e.g., assignments concerning children, lack of support from the colleague, and situations concerning threats and violence which they are unable to control [44,47]. Care situations where AS professionals are exposed to threats and violence are a growing concern [48] associated with varying patient encounters and situations [49].…”
Section: Work-related Emotional Demandsmentioning
confidence: 99%